A latent profile analysis of the Five Factor Model of personality: A constructive replication and extension. (1st March 2019) - Fisher, Peter A.; Robie, Chet
Abstract: Recent research into the underlying structure of personality has created considerable debate among academics. Further, a new, person-centered approach to studying personality has recently gathered support, but results have been underwhelming and inconsistent. The present study steps into the debate from a new angle with a constructive replication and derives a model of latent personality profiles in an archival sample of over three million respondents from almost every country in the world who completed a Five-Factor Model of personality questionnaire and other work and life outcomes measures. Three latent profiles emerged from this analysis, which were characterized by the degree to which respondents endorsed the traits of Conscientiousness, Extraversion, Agreeableness, and Emotional Stability. The trait of Openness to Experience did not appear to discriminate between the three latent profiles. Consistent with socioanalytic theory, evolutionary psychology, and more nascent theory on the general factor of personality, personality profiles were labelled as maladaptive, adaptive, and highly adaptive . More adaptive personality profiles were associated with higher life satisfaction, job self-efficacy, and passion towards work, as well as favorable value systems. Theoretical implications are subsequently discussed.